Criminological Analysis of the Crime of Theft by Actors Outside Gorontalo - Maharani Saskia Limonu (Universitas Negeri Gorontalo, 2021)
Abstract: This study aims to determine and analyze what factors cause the rise of criminal acts of theft whose perpetrators come from outside Gorontalo. The type of research used in this article is empirical legal research with a qualitative approach. Furthermore, the data will be analyzed descriptively by describing and providing interpretations of the data obtained in the field by basing on the applicable norms or legal rules associated with the subject matter studied, namely those concerning theft. The results of this study indicate that the factors that cause the rise of criminal acts of theft whose perpetrators come from outside Gorontalo are 1) Economic factors that result in unemployment and poverty. 2) The development of globalization and the lack of communication between the police and the sub-district government, the development of globalization moves feel so fast that people can quickly move from one place to another and this is accompanied by a surveillance system that exists in every border between provinces which is so free that it makes it easier for the movement of the people. criminals to move from one place to another. 3) Individual and Victim Factors, it is undeniable that every criminal act that occurs is also influenced by the victim's careless and careless factors so that it invites the intentions of the perpetrators of the crime.